Remaja dan tantangan zaman: Menjadikan Al-Qur’an sebagai panduan hidup - Auliya, Irva (Maliki Interdisciplinary Journal, 2025)
The Qur’an, as a life guide, provides clear directions for adolescents to face various challenges of modern life. This study aims to analyze the influence of Qur’anic teachings in shaping the character and morals of teenagers amid modern influences. Using a qualitative approach and literature review, this research finds that values in the Qur’an such as patience, honesty, trustworthiness, and integrity play a significant role in guiding teenagers to maintain good character, avoid promiscuity, and strengthen mental resilience in facing modern temptations. The Qur’an provides relevant and applicable guidance to form a strong character, which can serve as a shield against the social issues developing among teenagers. In conclusion, the teachings of the Qur’an offer strong moral support and are beneficial for adolescents in leading a better life.